ẒĀHIRAT AL-TAṬARRUF AL-DĪNĪY FĪ ‘ĀLAM AL-SHABĀB WA AL-TA‘ALĪM: Dirāsah ‘an Ṣ‘ūd al-Ḥarakah al-Islāmīyah al-Rādīkālīyah fī al-Madāris al-Thānawīyah fī Indūnīsiyā (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
The spread of radicalism-intolerance has entered into the recesses of the life of Indonesian people, especially in education field. This article aims to explore the facts of radicalism-intolerance at high school level in two major cities in Indonesia, Surabaya and Jakarta, and to analyze educational policies related to schools’ responses towards the phenomenon of radicalism. The data are collected by surveying and interviewing the leading figures of the Education and Culture Office of Surabaya and of Jakarta, high school principals, and high school teachers in Surabaya and Jakarta. The obtained data are then analyzed through focus group discussions (FGD) and logical thinking to find and analyze the subject matter in accordance with the focus of this study. The results show that (1) the indications of radicalism-intolerance had entered high school even though this remains at low level, (2) school managers, principals, and teachers had remarkable concerns and thorough vigilance towards their students exposed to radicalism- intolerance along with the rise of such a phenomenon in social and print media, and (3) the Ministry of Education and Culture firmly had not made so-called antiradicalism education policies as outlined in the blueprint of a curriculum.